Krótkowzroczność w schorzeniach ogólnoustrojowych - Mrugacz, Małgorzata; Rydzanicz, Małgorzata; Frajdenberg, Agata; Podfigurna-Musielak, Monika; Gajęcka, Marzena (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Myopia is the most common refractive error. Myopia has been well established as a multifactorial disease with both genetic and environmental etiology. A number of genetic loci have been linked with myopia. We have described the prevalence and the symptoms of systemic disorders associated with myopia, including: Stickler syndrome, Marfan syndrome, Ehlers-Danlos syndrome, Weill-Marchesani syndrome, homocystinuria, McCune-Albright syndrome, Kniest syndrome, Down syndrome, Prader-Willi syndrome, Noonan syndrome, Cohen syndrome, Rubinstein-Taybi syndrome, Cornelia de Lange syndrome and fetal alcohol syndrome.